PERANAN SISTIM INFORMASI MANAJEMEN BAGI ORGANISASI PUBLIK - warno, warno (potensio, 2009)
The development of public organizations in the context ofthe state administration has been so rapid in ManagementInformation Systems, both at the level of development ofboth theoretical and empirical context. Theoretically,organizational theory has evolved not only limited to formalorganizational terms, often associated with bureaucracy.Starting from the distinction Search Public and PrivateOrganizations, Public and Private OrganizationalCharacteristics and tried several approaches used to identifypublic organizations (Caiden, 1987). For public managementinformation systems. In the framework of managementinformation systems actually are two concepts that relatedirectly to decision-making, namely SDS, structured decisionsystem with the DSS, decision support system (Gorry andMorton in Golembiewski).Key words: management information systems, decisionstructurted system, DSS